(untitled) - Katz, Donald R. (New York, 1987)
Katz writes about the recent changes at Sears, Roebuck, the country's largest retailer. The chief protagonist is Edward Telling, chairman from 1977 through 1984. Faced with falling net income, under Telling Sears diversified beyond retail merchandising into retail financial and real estate services. The merchandise division shrank, and underwent an internal shakeup. Katz, who was given unlimited research access by Sears, devotes most of the book to the men who worked and fought at Sears headquarters in Chicago, but enlivens his reporting with notes from the checkout counter where he once worked. Recommended to public libraries. James W. Oberly, Univ . of Wisconsin - Eau Claire
Keywords: Sears, Roebuck and company